2007
DOI: 10.1063/1.2757410
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of prompt emission from GRBs with a photospheric component and its detectability by GLAST

Abstract: Abstract. The prompt emission from gamma-ray bursts (GRBs) still requires a physical explanation. Studies of time-resolved GRB spectra, observed in the keV-MeV range, show that a hybrid model consisting of two components, a photospheric and a non-thermal component, in many cases fits bright, single-pulsed bursts as well as, and in some instances even better than, the Band function. With an energy coverage from 8 keV up to 300 GeV, GLAST will give us an unprecedented opportunity to further investigate the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It has therefore been suggested that there is an interplay between different emission mechanisms, either alone or combined with each other (e.g. Mészáros & Rees 2000;Ryde 2005;Battelino et al 2007;Guiriec et al 2011Guiriec et al , 2013. It is then a natural consequence that subgroups of GRBs could exist, that are produced by different emission mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been suggested that there is an interplay between different emission mechanisms, either alone or combined with each other (e.g. Mészáros & Rees 2000;Ryde 2005;Battelino et al 2007;Guiriec et al 2011Guiriec et al , 2013. It is then a natural consequence that subgroups of GRBs could exist, that are produced by different emission mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that the hybrid model has been suggested for bursts in which both a thermal and a non-thermal component have been observed (e.g. Ryde 2005;Battelino et al 2007;Ryde & Pe'er 2009;Guiriec et al 2011;Iyyani et al 2013;Axelsson et al 2012;Burgess et al 2014;Nappo et al 2017). In these cases the magnetic energy is dissipated during the prompt phase, giving rise to emission observed in coincidence with the photospheric emission (e.g.…”
Section: Magnetic Content Of the Jetmentioning
confidence: 72%
“…This component is often interpreted as synchrotron emission (e.g. Mészáros & Rees 2000;Ryde 2005;Battelino et al 2007). The narrowest possible spectrum in the coasting phase, is from a passively cooled jet without any energy dissipation that can alter the spectrum.…”
Section: Transparency In the Coasting Phasementioning
confidence: 99%
“…The hybrid model, that may be interpreted as a combination of photospheric and optically-thin synchrotron radiation, fits the spectra of single-pulsed GRBs well [see 13,19]. The problem with the synchrotron "line of death" (α > −2/3) is avoided with this model, since the Rayleigh-Jeans portion of the blackbody component explains the hard spectral slopes seen in many BATSE bursts.…”
Section: Discussionmentioning
confidence: 98%
“…In our simulations for GLAST we extended the energy range into the GLAST domain, and therefore used an extended time-dependent hybrid model that included a blackbody function that evolves over time and a broken power-law -instead of a single power-law component -with a high-energy cut-off. The blackbody component that evolves over time is described by: We motivated the broken power-law based on the following two facts: a) OTS radiation may according to theory show a break in the energy domain covered by GLAST and b) power-law index values in the BATSE data from the hybrid model fits can be interpreted as being distributed around two values as shown in [19]. These two power law index values may be given a physical interpretation: the higher value (∼ 2.1) stems from a shock-accelerated distribution of electrons and the lower value (∼ 1.5) from the cooling electrons originating from the same distribution.…”
Section: The Hybrid Modelmentioning
confidence: 99%